The effect of confounding variables on the relationship between anthropometric and physiological features in 2000-m rowing ergometer performance - Podstawski, R.; Boryslawski, K.; Alföldi, Z.; Ferenc, I.; Wasik, J. (Frontiers in Physiology, 2023)
Background: Anthropometric and physiological characteristics are often considered as potential variables that are significantly related with motor performance.